An Enhanced Critical Path Method to solve Time-Cost Trade- Off using Type-2 Pentagonal Fuzzy numbers - P.Sakthi Priya, N.; Selva kumari, K. (International Journal of Engineering and Technology, 2018)
Critical path method is widely used for analyzing and managing task sequences in complex projects. Crashing is a schedule compression technique used to reduce the project duration.An approach has been made to decide the optimal crash plan to complete the project in minimal duration.Type-2 Pentagonal fuzzy numbers are used in the time-cost trade-off  problem which includes ranking process.The project crashing problem is solved using deterministic solution technique.